HIV Prevalence Among Patients of Sexually Transmitted Infection in A Tertiary Care Hospital in Western India - Hitesh M Shah; Amit S Mistry; Deepak D Umarigar (Medsci Publications, 2016)
Introduction: With rapid urbanization and Industrialization of our cities Sexually Transmitted Diseases (STD) and Human Immunodeficiency Virus (HIV) is becoming major public health problem. Present study was planned with following objectives to know the socio demographic profile of STD patients reporting to a tertiary care hospital during study period and to know HIV seropositivity amongst STD patients in a tertiary care hospital. Material and Methods: This was an observational, descriptive case study of total 240 patients with sexually transmitted diseases who attended dermatological department of New Civil Hospital, Surat in time period between January 2003 and June 2004. Observation: Total of 240 patients of STIs were evaluated. Male to female ration was 3.4:1. Majority of patients belongs to age group between 16-35 years of age group. Herpes progenitalis was commonest STI diagnosed (48.75). HIV seropositivity amongst studied patient was 18.3%. Commercial sex workers were most common source of infection. HIV sero positivity rate in migrant population was 17.56%. Conclusion: Migration, lower socio-economic status, level of education are important social factor for spread of STIs and HIV. Viral Sexually Transmitted Infections (STI)s were prevalent than Bacterial STIs in this study.